2017
DOI: 10.1016/j.jsv.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of cable-driven parallel robots based on the dynamic stiffness matrix method

Abstract: This paper focuses on the vibration analysis of Cable-Driven Parallel Robots (CDPRs). An oscillating model of CDPRs able to capture the dynamic behavior of the cables is derived using Lagrangian approach in conjunction with the Dynamic Stiffness Matrix method. Then, an original approach to analyze the modal interaction between the local cable modes and the global CDPR modes is presented. To illustrate this approach, numerical investigations and experimental analyses are carried out on a large-dimension 6-DOF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…With the increasing use of robots in various applications, the need for structures that have no limitations of series robots and with special features such as precision, acceleration and high load-carrying capability have been considered more than ever. Parallel robot mechanism is connected end-effector with several closed loop kinematic chain to the base [2]. Due to various weakness of series and parallel robotics such as small workspace, capable of carrying much more than the usual robots and high cost of installation and maintenance, many industries are still not equipped to robotics [3].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing use of robots in various applications, the need for structures that have no limitations of series robots and with special features such as precision, acceleration and high load-carrying capability have been considered more than ever. Parallel robot mechanism is connected end-effector with several closed loop kinematic chain to the base [2]. Due to various weakness of series and parallel robotics such as small workspace, capable of carrying much more than the usual robots and high cost of installation and maintenance, many industries are still not equipped to robotics [3].…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of CDPRs simulated with lumped mass or continuous mass cable modeling, e.g. [51][52][53], have recently attracted more interests. However, since quasi-static operation is assumed in the present work, the classic elastic catenary cable model [5] is considered in order to take into account the cable mass and elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Because the corresponding inverse kinetostatic problem is difficult to solve in real-time, assuming that the cable sag is relatively small, a simplified modeling of cables of non-negligible mass can be considered [54]. Compared to the use of the full elastic catenary cable model, it leads to a simplified static analysis of large-dimension CDPRs [47,55] which is of significant interest for real-time control purposes and for vibration analysis [53].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] The SSA of CDM is aiming to analyze and improve the static positioning accuracy, [16][17][18] especially for the pick-and-place application, 19 such as the CoGiRo. 18 The purpose of DSA of CDM is to analyze the vibration of those applications [15][16][17] requiring high performances, especially dynamic performances, 16 such as high-speed FALCON 20 and large radio telescope FAST (Five-hundred-meter Aperture Spherical radio Telescope). 21 Whether SSA or DSA, cable modeling should be studied first.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The third model is used for high-speed, large-dimension, or heavy-load CDM. 16,[23][24][25][26][27][28] Previous researches have shown that the sagging cable model is divided into two-dimensional inclined cable [16][17][18][19]29 and three-dimensional inclined cable. 15,23,30 Riehl et al 29 analyzed the influence of the sagging cable model on the end-effector positioning, the control lengths of the cables, and the cable tensions.…”
Section: Introductionmentioning
confidence: 99%